Catalytic and heat-insulating multifunctional aerogel and preparation method thereof
Catalysis with a 'brick sand' structure was prepared by using hydrothermal reaction of alumina nanopowder and acidic solution under high temperature environments and mixing hydrophobic nanotitanium dioxide, chopped fibers and glass powder, combined with mold mold molding and supercritical drying. , Heat-insulated multifunctional aerogel solves the problems of brittleness and thermal conductivity of traditional aerogel materials at high temperatures, and achieves high strength, low thermal conductivity and high temperature resistance.
Patent Information
- Application Number
- CN202411138862.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-07
AI Technical Summary
The existing aerogel materials have problems such as brittleness, high thermal conductivity and insufficient structural strength in high temperature environments, and the preparation efficiency of traditional catalytic functional aerogels is low and uneven.
Using hydrothermal reaction of alumina nanopowder with acidic solution, combined with the mixture of hydrophobic nanotitanium dioxide, chopped fibers and glass powder, the thermal treatment is carried out through mold setting and supercritical drying to prepare a 'brick sand' structure. Catalytic and thermally insulated multifunctional aerogel.
The high strength, infrared radiation resistance, low thermal conductivity and high temperature resistance of the material are achieved, avoiding the cost and cycle of settlement and machining, and having good catalytic and thermal insulation properties.
Smart Images

Figure CN119263783A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel preparation, and in particular to a catalytic and heat-insulating multifunctional aerogel and a preparation method thereof. Background Art
[0002] Nanoporous aerogel (abbreviated as aerogel) is a gel material whose dispersion medium is gas. It is a nanoporous solid material with a network structure composed of colloidal particles or polymer molecules. The size of the pores in the material is in the nanometer order of magnitude. At present, the most widely used field of aerogel is still the field of thermal insulation, because the unique nanostructure of aerogel can effectively reduce convection conduction, solid phase conduction and thermal radiation.
[0003] Most traditional aerogel materials are pearl necklace-like structures formed by the accumulation of nanoparticles. Aerogel materials with this structure are brittle and require fiber reinforcement to achieve structural strengthening in practical applications. However, the fiber reinforcement process will increase the density, increase the solid phase thermal conductivity and increase the complexity of the process. In addition, there are some skeleton strengthening methods to prepare pure phase aerogel materials with good structural strength. However, this method often requires a high-temperature sintering process to increase the skeleton size to improve the strength of the material, which will bring new problems such as high thermal conductivity and high brittleness. Nanocellulose can prepare nanocellulose aerogels with certain structural toughness to a certain extent, but the organic component determines that its temperature resistance is poor and is not suitable for high-temperature insulation applications. Therefore, it is of great significance to develop a nano aerogel material with good structural toughness. The patent "A kind of alumina nanowire aerogel insulation material and its preparation method (CN202010669268.X)" applied by the inventor adopts a hydrothermal method to prepare an alumina nanowire precursor solution containing acidic silica sol and boric acid, and the preparation of alumina nanowire aerogel is achieved through freeze drying and heat treatment. The aerogel prepared by freeze-drying in this preparation method has larger pores and no secondary structure is constructed, so its gas phase heat conduction is larger.
[0004] With the development of science and technology, various fields have put forward higher requirements on the strength, versatility and thermal insulation performance of thermal insulation materials. Especially in high temperature environments, radiation heat transfer is dominant. Therefore, it is very necessary to develop an effective method to prepare a lightweight, high-strength, multifunctional, radiation-resistant nano thermal insulation material. Traditional catalytic functional aerogels, titanium dioxide aerogels prepared by hydrolysis and condensation, are mostly anatase crystals with low catalytic efficiency. Directly doping the rutile phase to prepare hybrid aerogels to improve the catalytic effect is prone to precipitation problems in the preparation, and it is impossible to obtain a homogenized, catalytic aerogel.
[0005] The present invention is inspired by the microstructure of shells and constructs a brick-sand structure, with aluminum oxide nanowires as bricks and titanium oxide nanopowder as sand. This special microstructure determines that its macroscopic structural properties can exhibit high strength and resistance to infrared radiation. Summary of the invention
[0006] In order to solve the technical problems existing in the prior art, the present invention provides a catalytic and heat-insulating multifunctional aerogel with simple preparation process, good high-temperature resistance and light weight, and a preparation method thereof.
[0007] In a first aspect, the present invention provides a method for preparing a catalytic and heat-insulating multifunctional aerogel, the method comprising the following steps:
[0008] (1) mixing aluminum oxide nanopowder and an acidic solution in deionized water, and obtaining a uniform mixed solution by high-speed shear stirring and ultrasonic treatment;
[0009] The specific steps are as follows: dissolving aluminum oxide nanopowder with a diameter distribution of 10 to 100 nm in water, adding sulfuric acid solution of 1% by mass of the total solution, the concentration range of the sulfuric acid solution is 0.1 to 30 mol / L, and the mass fraction of the aluminum oxide nanopowder in the mixed solution is 5% to 20%;
[0010] (2) placing the mixed solution in a sealed container and performing a hydrothermal reaction at 150 to 300° C. for 1 to 48 hours to obtain a semi-solid gel block;
[0011] The specific steps are as follows: the reaction must be carried out under fully closed conditions, and the container material must be a polymer material that does not react with the system;
[0012] (3) adding hydrophobic nano-titanium dioxide (rutile), chopped fibers and glass powder to the above gel block, mixing them thoroughly, and forming a new semi-solid gel block by mechanical stirring;
[0013] The specific steps are as follows: the gel block obtained in step 2 is first fully mixed with chopped fibers (5% to 50% of the mass of the gel block) and glass powder (1% to 20% of the mass of the gel block) for 0.1 to 4 hours, and then the hydrophobic nano titanium dioxide (rutile) is added and the mixing is continued for 0.1 to 4 hours to obtain a new semi-solid gel block;
[0014] (4) shaping the new gel block obtained in step (3) using a mold as required;
[0015] The specific steps are as follows: add the new gel block into the metal mold coated with a release agent, use a tool to flatten and fill the material body, then close the mold, apply a certain pressure to achieve shaping, and the pressure is controlled at 0.1-5MPa;
[0016] (5) performing a solvent replacement process and a supercritical drying process on the shaped block to obtain an aerogel preform;
[0017] The specific steps are: using ethanol as a solvent for solvent replacement, the amount of solvent used is 8 to 10 times the volume of the gel block after shaping, the replacement times are 3 to 5 times, and after the solvent replacement process is completed, a carbon dioxide supercritical drying process is performed, the supercritical drying temperature is 20 to 60°C, and the pressure is 10 to 16Mpa;
[0018] (6) subjecting the aerogel preformed material to a graded heat treatment process to obtain a catalytic and heat-insulating multifunctional aerogel;
[0019] The specific steps are: heat treating the aerogel prefabricated material in an inert atmosphere at a temperature of 600° C. for 0.5 to 2 hours, and then continuing to heat up to 1000 to 1200° C. for 0.5 to 2 hours.
[0020] The above steps realize the preparation of a catalytic and heat-insulating multifunctional aerogel.
[0021] In a second aspect, the present invention provides a catalytic and heat-insulating multifunctional aerogel material prepared by the preparation method described in the first aspect of the present invention.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] (1) Compared with traditional pearl necklace-shaped aerogel materials, the present invention has better mechanical strength. Inspired by the microstructure of shells, the "brick-sand" structure constructed by the present invention is composed of nanowires entangled with each other, and glass powder is used as an adhesive to form bonding nodes at the overlap of nanofibers, greatly improving the structural strength of the material.
[0024] (2) The present invention adopts a multi-level structure assembled with three structures of micron fiber, nano fiber and nano particle as basic units. The hydrophobic nano particles form clusters similar to emulsions during the mixing process. The nano particles increase the solid phase heat conduction path and reduce the gas phase heat conduction. At the same time, titanium oxide can effectively resist infrared radiation at high temperature as a good anti-infrared radiation agent. The nano fiber skeleton can play a good supporting role and can achieve efficient heat insulation effect under high strength conditions.
[0025] (3) Titanium dioxide nanoparticles are dispersed in the aerogel prepared by the present invention, which can take into account the catalytic effect.
[0026] (4) The mixed matrix in the present invention is semi-solid and has high viscosity, which avoids the sedimentation of nanopowders in the dispersion system.
[0027] (5) The aerogel material obtained in the preparation process of the present invention from gelation, post-treatment process to supercritical drying does not have any dimensional shrinkage, and the net size molding of the product can be achieved, avoiding the cost and cycle increase caused by the mechanical processing process.
[0028] (6) In the present invention, the alumina nanowire solution, glass powder and ceramic fiber are first dispersed into an aqueous solution, and hydrophobic nano-titanium dioxide (rutile) is used as the hydrophobic dispersed phase to achieve two controllable components, realize the selective bonding of the glass powder, and ensure the efficient thermal insulation of the nanoparticles on the material.
[0029] (7) The aerogel material prepared by the method of the present invention adopts a segmented heat treatment process, which slows down the crystal transformation process of the material and avoids the structural collapse of the porous structure during rapid shrinkage. At the same time, the doping of nanoparticles is physical doping without chemical cross-linking. The sintering effect at high temperature will not affect the overall skeleton. Therefore, there is no obvious volume shrinkage at high temperature and the material has good temperature resistance.
[0030] (8) The titanium dioxide (rutile) nanoparticles doped in the present invention exist in the form of hydrophobic particle clusters, which can effectively resist the effects of infrared radiation and greatly improve the high-temperature thermal insulation performance of the thermal insulation material.
[0031] (9) The aerogel material prepared by the method of the present invention has excellent high temperature resistance while maintaining a low thermal conductivity of less than 0.026 W / mK, and can be used for long-term thermal insulation at 1100°C.
[0032] (10) The porosity of the nanowire aerogel material prepared by the method of the present invention is above 98%, the pore size is 5 to 500 nm, the diameter of the nanowire of the aerogel is 30 to 200 nm, and the specific surface area at high temperature is 100 to 600 m 2 / g, the heat resistance temperature is above 1100℃, and the high temperature thermal conductivity is as low as 0.055W / mK. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a preparation flow chart of the present invention.
[0034] Figure 2 This is a schematic diagram of the structure of the shell-like "brick sand" prepared by the present invention
[0035] Figure 3 This is a SEM image of the nanowire portion prepared in Example 1. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.
[0038] Example 1
[0039] (1) mixing aluminum oxide nanopowder and an acidic solution in deionized water, and obtaining a uniform mixed solution by high-speed shear stirring and ultrasonic treatment;
[0040] The specific steps are as follows: dissolving aluminum oxide nanopowder with a diameter distribution of 10 to 15 nm in water, adding sulfuric acid solution of 1% by mass of the total solution, the concentration range of the sulfuric acid solution is 10 mol / L, and the mass fraction of aluminum oxide nanopowder in the mixed solution is 8%;
[0041] (2) placing the mixed solution in a sealed container and performing a hydrothermal reaction at 230° C. for 5 h to obtain a semi-solid gel block;
[0042] The specific steps are as follows: the reaction must be carried out under fully closed conditions, and the container material must be a polymer material that does not react with the system;
[0043] (3) adding hydrophobic nano-titanium dioxide (rutile), chopped fibers and glass powder to the above gel block, mixing them thoroughly, and forming a new semi-solid gel block by mechanical stirring;
[0044] The specific steps are as follows: the gel block obtained in step 2 is first fully mixed with chopped fibers (10% of the mass of the gel block) and glass powder (10% of the mass of the gel block) for 0.1 to 4 hours, and then hydrophobic nano-titanium dioxide (rutile) (3% of the mass of the gel block, chopped fibers and glass powder) is added, and the mixing is continued for 0.1 to 4 hours to obtain a new semi-solid gel block;
[0045] (4) shaping the new gel block obtained in step (3) using a mold as required;
[0046] The specific steps are as follows: add the new gel block into the metal mold coated with a release agent, use a tool to flatten and fill the material body, then close the mold, apply a certain pressure to achieve shaping, and the pressure is controlled at 0.9-1.1MPa;
[0047] (5) performing a solvent replacement process and a supercritical drying process on the shaped block to obtain an aerogel preform;
[0048] The specific steps are as follows: using ethanol as solvent for solvent replacement, the amount of solvent used is 10 times the volume of the gel block after shaping, the replacement times are 3 times, and after the solvent replacement process is completed, a carbon dioxide supercritical drying process is performed, the supercritical drying temperature is 40°C, and the pressure is 15Mpa;
[0049] (6) subjecting the aerogel preformed material to a graded heat treatment process to obtain a catalytic and heat-insulating multifunctional aerogel;
[0050] The specific steps are: heat treating the aerogel prefabricated material in an inert atmosphere at a temperature of 600° C. for 2 h, and then continuing to heat up to 1100° C. for 2 h.
[0051] The catalytic and heat-insulating multifunctional aerogel prepared in Example 1 has good structural strength. The catalytic and heat-insulating multifunctional aerogel in Example 1 was tested for its heat insulation performance, and it was found that its surface had no gloss loss, no discoloration, and no shedding. Other performance indicators are shown in Table 1.
[0052] Example 2
[0053] Example 2 is substantially the same as Example 1, except that: during the preparation of the dispersion in step 1, no glass powder is added.
[0054] The strength of the aerogel-based thermal insulation material prepared in Example 2 is slightly weaker than that in Example 1, but it can also form a complete block. Other performance indicators are shown in Table 1.
[0055] Example 3
[0056] Example 3 is basically the same as Example 1, except that: during the preparation of the dispersion in step 1, 10 mol / L acetic acid solution is added to account for 1% of the total solution mass.
[0057] The strength of the aerogel-based thermal insulation material prepared in Example 3 is relatively weak and no relatively complete block is formed. Other performance indicators are shown in Table 1.
[0058] Example 4
[0059] Example 4 is substantially the same as Example 1, except that during the preparation of the nano-dispersion solution in step 1, 0.5% of the total solution mass of a 10 mol / L sulfuric acid solution is added.
[0060] The aerogel-based thermal insulation material in Example 4 has weak strength and powdering phenomenon. Other performance indicators are shown in Table 1.
[0061] Example 5
[0062] Example 5 is basically the same as Example 1, except that no chopped fibers are added during the mixing process with the gel block to obtain an aerogel-based thermal insulation material.
[0063] The aerogel-based thermal insulation material in Example 5 is relatively strong but brittle. Other performance indicators are shown in Table 1.
[0064] Example 6
[0065] Example 6 is basically the same as Example 1, except that no nano titanium dioxide (rutile) is added during the mixing process with the gel block to obtain an aerogel-based thermal insulation material.
[0066] The aerogel-based thermal insulation material in Example 6 has relatively strong strength, and other performance indicators are shown in Table 1.
[0067] Example 7
[0068] Example 7 is basically the same as Example 1, except that hydrophilic nano-titanium dioxide (rutile) is added during the mixing process with the gel block instead of hydrophobic nano-titanium dioxide (rutile) to obtain an aerogel-based thermal insulation material.
[0069] The aerogel-based thermal insulation material in Example 7 has a relatively strong strength, and a thermal insulation performance test was conducted, and it was found that its thermal conductivity was relatively high. Other performance indicators are shown in Table 1.
[0070] Example 8
[0071] Example 8 is substantially the same as Example 1, except that no graded heat treatment is performed to obtain an aerogel-based thermal insulation material.
[0072] The aerogel-based thermal insulation material in Example 8 can maintain structural integrity, but does not have high strength characteristics. Other performance indicators are shown in Table 1.
[0073] Example 9
[0074] Example 9 is substantially the same as Example 1, except that the solvent replacement process in step 4 is not performed to obtain an aerogel-based thermal insulation material.
[0075] The thermal insulation performance of the nano-aerogel material in Example 9 was tested, and it was found that the aerogel was powdered and difficult to shape. Other performance indicators are shown in Table 1.
[0076] Example 10
[0077] Example 10 is basically the same as Example 1, except that the supercritical drying process in step 4 is not performed, and normal pressure drying is performed instead to obtain the nanowire aerogel material.
[0078] The nano aerogel material in Example 10 has a larger shrinkage and a higher density. Other performance indicators are shown in Table 1.
[0079] Comparative Example 1: "A high temperature resistant and high strength nanowire aerogel material and its preparation method (CN202210563030.8)"
[0080] ① Aluminum oxide nanopowder with a particle size range of 10 to 15 nm, boron nitride nanosheets with a particle size range of 1 to 2 μm and a thickness range of 60 to 120 nm, and a sulfuric acid solution with a concentration of 10 mol / L are mixed in deionized water, and mixed evenly by stirring and ultrasonication to obtain a mixed solution; in the mixed solution, the mass percentage of the aluminum oxide nanopowder is 8%, the mass percentage of the boron nitride nanosheets is 2%, and the amount of the sulfuric acid solution accounts for 1% of the total weight of the mixed solution.
[0081] ② Place the above mixed solution in a sealed container and perform hydrothermal reaction at 230°C for 15 hours to obtain a semi-solid gel.
[0082] ③ The gel was immersed in a silica sol solution for 24 hours, and then the block was placed in a sealed container and aged in a 90°C oven for 24 hours; during the immersion, the liquid surface of the silica sol solution was made to cover the gel; the silica sol solution was prepared as follows: the mass ratio of acidic silica sol to ammonium fluoride solution was 100:4, and the ammonium fluoride solution was added to the acidic silica sol and mixed for 2 hours to obtain a silica sol solution with a solid content of 10%, and the concentration of the ammonium fluoride solution was 1.5 mol / L.
[0083] ④ The treated gel block obtained in step ③ is subjected to a solvent replacement process and a supercritical drying step to obtain a boron nitride-doped nanowire aerogel material; the specific steps are: ethanol is used as the solvent for solvent replacement, and the replacement is performed 3 times according to 10 times the volume of the gel block, and then a supercritical carbon dioxide drying process is performed, and the supercritical drying temperature is 50°C and the pressure is 14MPa.
[0084] ⑤ The boron nitride-doped nanowire aerogel material is heat-treated in an inert atmosphere at a temperature of 1150° C. for 0.5 h to obtain a high-temperature resistant and high-strength nanowire aerogel material.
[0085] Table 1: Performance indicators of a catalytic and heat-insulating multifunctional aerogel prepared in Examples 1 to 10 and the heat-insulating material of the comparative example
[0086]
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a catalytic and heat-insulating multifunctional aerogel, characterized in that The method comprises the following steps: (1) mixing aluminum oxide nanopowder and an acidic solution in deionized water, and obtaining a uniform mixed solution by high-speed shear stirring and ultrasonic treatment; (2) placing the mixed solution in a sealed container and performing a hydrothermal reaction at 150 to 300° C. for 1 to 48 hours to obtain a semi-solid gel block; (3) adding hydrophobic nano-titanium dioxide (rutile), chopped fibers and glass powder to the above gel block, mixing them thoroughly, and forming a new semi-solid gel block by mechanical stirring; (4) shaping the new gel block obtained in step (3) using a mold as required; (5) performing a solvent replacement process and a supercritical drying process on the shaped block to obtain an aerogel preform; (6) The aerogel preform material is subjected to a graded heat treatment process to obtain a catalytic and heat-insulating multifunctional aerogel.
2. The preparation method according to claim 1, wherein in step (1), aluminum oxide nanopowder having a diameter distribution in the range of 10 to 100 nm is dissolved in water, and a sulfuric acid solution accounting for 1% of the total solution mass is added, the concentration range of the sulfuric acid solution is 0.1 to 30 mol / L, and the mass fraction of the aluminum oxide nanopowder in the obtained mixed solution is 5% to 20%.
3. According to the preparation method of claim 1, in step (2), the reaction must be carried out under fully closed conditions, and the container material is a polymer material that does not react with the system.
4. The preparation method according to claim 1, in step (3), the gel block obtained in step (2) is first fully mixed with chopped fibers and glass powder for 0.1 to 4 hours, and then hydrophobic nano-titanium dioxide (rutile) is added and mixed for another 0.1 to 4 hours to obtain a new semi-solid gel block.
5. The preparation method according to claim 1, in the corresponding step (4), the new gel block obtained in step (3) is added into a metal mold coated with a release agent, the material body is flattened and filled with a tool, and then the mold is closed and a certain pressure is applied to achieve shaping, and the pressure is controlled at 0.1 to 5 MPa.
6. The preparation method according to claim 1, wherein in step (5), ethanol is used as the solvent for solvent replacement, the amount of the solvent used is 8 to 10 times the volume of the block after shaping, the number of replacements is 3 to 5 times, and after the solvent replacement process is completed, a carbon dioxide supercritical drying process is performed, the supercritical drying temperature is 20 to 60° C., and the pressure is 10 to 16 MPa.
7. The preparation method according to claim 1, wherein in step (6), a graded heat treatment process is performed, wherein the treatment system is in an inert atmosphere, the treatment temperature is 600°C, the treatment time is 0.5 to 2 hours, and then the temperature is continued to rise to 1000 to 1200°C, and the treatment time is 0.5 to 2 hours.
8. A catalytic and heat-insulating multifunctional aerogel, which is obtained by the preparation method according to any one of claims 1 to 7, wherein the porosity of the aerogel is above 98%, the pore size is 5 to 500 nm, the nanowire diameter is 30 to 200 nm; while maintaining a low thermal conductivity of less than 0.026 W / mK, it can achieve long-term heat insulation application at 1100°C; and the specific surface area at high temperature is 100 to 600 m 2 / g, the heat resistance temperature is above 1100℃, and the high temperature thermal conductivity is as low as 0.055W / mK.
Citation Information
Patent Citations
An alumina nanowire aerogel thermal insulation material and its preparation method
CN111848140B
A high-temperature resistant, high-strength, and high-toughness nanowire aerogel material and its preparation method
CN114804816B
An improved process for producing silica aerogel thermal insulation product with increased efficiency
CN107849764A
Aluminum oxide nanowire aerogel thermal insulation material and preparation method thereof
CN111848140A
Hydrophobic ceramic aerogel material with micro-nano structure and preparation method of hydrophobic ceramic aerogel material
CN114853453A